Antibiotic resistance patterns of bacteria causing urinary tract infections in the elderly living in nursing homes versus the elderly living at home: an observational study - Fagan, Mark (BMC Geriatr, 2015)
BACKGROUND: Antibiotic resistance is a problem in nursing homes. Presumed urinary tract infections (UTI) are the most common infection. This study examines urine culture results from elderly patients to see if specific guidelines based on gender or whether the patient resides in a nursing home (NH) are warranted. METHODS: This is a cross sectional observation study comparing urine cultures from NH patients with urine cultures from patients in the same age group living in the community. RESULTS: There were 232 positive urine cultures in the NH group and 3554 in the community group. Escherichia coli was isolated in 145 urines in the NH group (64 %) and 2275 (64 %) in the community group. There were no clinically significant differences in resistance. Combined, there were 3016 positive urine cultures from females and 770 from males. Escherichia coli was significantly more common in females 2120 (70 %) than in males 303 (39 %)(p < 0.05). Enterococcus faecalis was significantly less common in females 223(7 %) than males 137 (18 %) (p < 0.05). For females, there were lower resistance rates to ciprofloxacin among Escherichia coli (7 % vs 12 %; p < 0.05) and to mecillinam among Proteus mirabilis (3 % vs 12 %; p < 0.05). CONCLUSIONS: Differences in resistance rates for patients in the nursing home do not warrant separate recommendations for empiric antibiotic therapy, but recommendations based on gender seem warranted.